Lumenal interactions in nuclear pore complex assembly and stability - Yewdell, William T. (The American Society for Cell Biology, 2011)
Nuclear pore complexes (NPCs) provide a gateway for the selective transport of macromolecules across the nuclear envelope (NE). Although we have a solid understanding of NPC composition and structure, we do not have a clear grasp of the mechanism of NPC assembly. Here, we demonstrate specific defects in nucleoporin distribution in strains lacking Heh1p and Heh2p—two conserved members of the LEM (Lap2, emerin, MAN1) family of integral inner nuclear membrane proteins. These effects on nucleoporin localization are likely of functional importance as we have defined specific genetic interaction networks between HEH1 and HEH2, and genes encoding nucleoporins in the membrane, inner, and outer ring complexes of the NPC. Interestingly, expression of a domain of Heh1p that resides in the NE lumen is sufficient to suppress both the nucleoporin mislocalization and growth defects in heh1Δpom34Δ strains. We further demonstrate a specific physical interaction between the Heh1p lumenal domain and the massive cadherin-like lumenal domain of the membrane nucleoporin Pom152p. These findings support a role for Heh1p in the assembly or stability of the NPC, potentially through the formation of a lumenal bridge with Pom152p.